Analysis of the colors used in the new cup-ramyeon package designs and their correspondence to flavor descriptions - 윤정우(Yoon, Jungwoo) (Journal of Basic Design & Art, 2019)
As the variety of styles and flavors of ramyeon(ramen) increase, analysis needs to be conducted of the use of color on packaging and how it portrays flavor. This is especially important as there has been an increase in the non-traditional styles of ramyeon. This study analyzes how new styles of cup ramyeon describe flavor through the use of color on packaging. Eight cup-ramyeon products were selected to serve as the samples most applicable to the concerns of this particular study. All samples were analyzed in terms of overall color, dominant color(background color), illustration, logo background, and logo. A two-part survey was conducted: Part A collected information about color without visual reference to packaging, whereas Part B used images of cup-ramyeon packaging photoshopped to display only color. Six findings have been noted as result of the investigation. First, cup-ramyeon packaging that displays colors similar to the color of the main ingredient or ingredients, like miyeok gook ramyeon and gyaeran tang myeon, allowed the survey subjects to easily predict how the product would taste. Second, certain food items and flavors could also be triggered by the particular color or colors used by a brand or product line, such as Ottugi Curry Ramyeon and other Ottugi curry products. Third, intensity of flavor can be portrayed by accent colors and the proportion of background/dominant colors to depiction colors. Fourth, utilizing colors or color combinations of food item packaging in similar categories can provide information about the flavor of a product. Fifth, creating ramyeon packaging in “sweet”(i.e., in terms of flavor) color combinations can signal that a product is bibim-style ramyeon without broth or soup. Lastly, using colors that are unfamiliar or rarely associated with Korean food does not provide any distinct notion of the product’s flavor. The analysis and results of this survey will be beneficial to future designs of ramyeon packaging, especially in terms of the use of color selection and combination to describe the flavor of new styles of ramyeon. KCI Citation Count: 0